Noninvasive Monitoring of the Response of Human Lungs to Low‐Dose Lipopolysaccharide Inhalation Challenge Using MRI: A Feasibility Study. Issue 6 (15th November 2019) - Kern, Agilo L.; Biller, Heike; Klimeš, Filip; Voskrebenzev, Andreas; Gutberlet, Marcel; Renne, Julius; Müller, Meike; Holz, Olaf; Wacker, Frank; Hohlfeld, Jens M.; Vogel‐Claussen, Jens
Abstract : Background: Development of antiinflammatory drugs for lung diseases demands novel methods for noninvasive assessment of inflammatory processes in the lung. Purpose: To investigate the feasibility of hyperpolarized 129 Xe MRI, 1 H T1 time mapping, and dynamic contrast‐enhanced (DCE) perfusion MRI for monitoring the response of human lungs to low‐dose inhaled lipopolysaccharide (LPS) challenge compared to inflammatory cell counts from induced‐sputum analysis. Study Type: Prospective feasibility study. Population: Ten healthy volunteers underwent MRI before and 6 hours after inhaled LPS challenge with subsequent induced‐sputum collection. Field Strength/Sequences: 1.5T/hyperpolarized 129 Xe MRI: Interleaved multiecho imaging of dissolved and gas phase, ventilation imaging, dissolved‐phase spectroscopy, and chemical shift saturation recovery spectroscopy. 1 H MRI: Inversion recovery fast low‐angle shot imaging for T1 mapping, time‐resolved angiography with stochastic trajectories for DCE MRI. Assessment: Dissolved‐phase ratios of 129 Xe in red blood cells (RBC), tissue/plasma (TP) and gas phase (GP), ventilation defect percentage, septal wall thickness, surface‐to‐volume ratio, capillary transit time, lineshape parameters in dissolved‐phase spectroscopy, 1 H T1 time, blood volume, flow, and mean transit time were determined and compared to cell counts. Statistical Tests: Wilcoxon signed‐rank test, Pearson correlation. Results: The percentage of neutrophils in sputum was markedly increased after LPS inhalation compared to baseline, P = 0.002. The group median RBC‐TP ratio was significantly reduced from 0.40 to 0.31, P = 0.004, and 1 H T1 was significantly elevated from 1157.6 msec to 1187.8 msec after LPS challenge, P = 0.027. DCE MRI exhibited no significant changes in blood volume, P = 0.64, flow, P = 0.17, and mean transit time, P = 0.11. Data Conclusion: Hyperpolarized 129 Xe dissolved‐phase MRI and 1 H T1 mapping may provide biomarkers for noninvasive assessment of the response of human lungs to LPS inhalation. By its specificity to the alveolar region, hyperpolarized 129 Xe MRI together with 1 H T1 mapping adds value to sputum analysis. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;51:1669–1676.